2021
DOI: 10.1177/23259671211041359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Ulnar Collateral Ligament Reconstruction in Major League Baseball Pitchers

Abstract: Background: The coronavirus disease of 2019 (COVID-19) pandemic led to the suspension and shortening of the 2020 Major League Baseball (MLB) season from 162 to 60 regular season games. The effect of this disruption on injury rates, specifically injury to the ulnar collateral ligament (UCL), has not been quantified. Purpose/Hypothesis: The purpose of this study was to compare the rate of UCL reconstruction (UCLR), surgery timing, and pitching workload in MLB pitchers from before and after the COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…German Professional Bundesglia Soccer League players had a greater than three times higher rate of injury when controlling for games played compared with injury rates prelockdown (27). In professional baseball players, the overall injury incidence rate in the upper extremities and spine/core was nearly twice that in pitchers and fielders during their shortened 2020 season compared with the two prior seasons (39), and pitchers were 2.9 times more likely to undergo ulnar collateral ligament surgery after the lockdown compared with the previous three years (40,41). Retrospective evidence from the NFL showed that the injury rate of players during weeks 1 to 4 of the 2020 to 2021 regular seasons was higher than that of the three prior preseasons and regular seasons (40).…”
Section: Lockdown Effect On Training Programs and Musculoskeletal Injurymentioning
confidence: 99%
“…German Professional Bundesglia Soccer League players had a greater than three times higher rate of injury when controlling for games played compared with injury rates prelockdown (27). In professional baseball players, the overall injury incidence rate in the upper extremities and spine/core was nearly twice that in pitchers and fielders during their shortened 2020 season compared with the two prior seasons (39), and pitchers were 2.9 times more likely to undergo ulnar collateral ligament surgery after the lockdown compared with the previous three years (40,41). Retrospective evidence from the NFL showed that the injury rate of players during weeks 1 to 4 of the 2020 to 2021 regular seasons was higher than that of the three prior preseasons and regular seasons (40).…”
Section: Lockdown Effect On Training Programs and Musculoskeletal Injurymentioning
confidence: 99%
“…Recently, increased injury rates have been documented following COVID-19 sports suspension in American Major League Baseball [ 21 , 22 ] and the National Football League [ 23 , 24 ]. European reports did not acknowledge the potential complicating factor of the effects of increases in the acute-to-chronic workload ratio (ACWR).…”
Section: Discussionmentioning
confidence: 99%
“…Hip replacements are generally the most common elective procedure, but elective procedures were halted and therefore most institutions did not perform them. Hip fractures have still been very common during this time[ 4 , 25 , 28 ]; however, the pandemic has increased the mortality and complication rate particularly amongst COVID-positive patients[ 5 , 8 , 11 , 16 , 38 ]. The importance of early treatment and proper rehabilitation was strongly emphasized in order to ensure prompt recovery[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al [ 38 ] studied the effect of COVID-19 on ulnar collateral ligament repair (UCLR) in 106 major league baseball (MLB) players. The study observed at all pitchers of the MLB who underwent UCLR repair and found no difference in overall UCLR repair from baseball seasons 2017 through 2020 ( n = 16, 20, 16, and 18).…”
Section: Clinical Presentationsmentioning
confidence: 99%